'The Free-Flying Natural Woman Boobs of Yore'? the Body Beyond Representation in Feminist Accounts of Objectification. Issue 1 (November 2020) - McCann, Hannah
This article takes up references to breasts as a key case study to examine white Western feminist debate around embodiment and objectification. Tracking shifting understandings of 'the gaze' in these accounts, we find that objectification is often rendered singular, ahistorical and, increasingly, individually internalised. The history of these approaches to objectification helps to explain why during the early 2000s, theorisations of feminist politics-lost were often rhetorically located alongside discussions of surgically modified breasts as a symbol of a new era of 'fake' feminism. In contrast, the 2010s saw several feminist movements premised on exposure of flesh and claims to individual recuperation of bodily autonomy. This article contends that both of these perspectives rely on a notion, built over successive eras of white Western feminist thought, that political work can and ought to be done through the body as a site of representational politics. This article subsequently offers a brief insight into how we might queer our approach to breasts to better account for the messiness of experiences of the flesh, considering the personal as political, while not investing in the body as the site where politics must be enacted.